2009
DOI: 10.1016/j.jtcvs.2009.05.037
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modeling of nonhypoxic cold ischemia–reperfusion simulating lung transplantation

Abstract: Objective Although anoxia/reoxygenation of cultured cells has been employed to model lung ischemia-reperfusion injury (IRI), this does not accurately mimic events experienced by lung cells while a lung is retrieved from a donor, stored, and transplanted. We developed an in vitro model of non-hypoxic IRI to simulate these events. Methods Human umbilical vein endothelial cells (HUVECs) underwent simulated cold ischemia by replacing 37°C culture media with 4°C Perfadex™ solution for 5 hours in 100% O2. Culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Simulated reperfusion resulted in activation of MAPKs and NF-κB and expression of interleukin (IL)-6 and IL-8 by endothelial cells. 20 In addition, in a cell culture model of simulated warm ischemia, inter-endothelial cell gap formation was prevented by a competitive TLR4 antagonist, implicating a direct link between pulmonary edema and TLR signaling. 19 …”
Section: Epithelium and Endotheliummentioning
confidence: 97%
“…Simulated reperfusion resulted in activation of MAPKs and NF-κB and expression of interleukin (IL)-6 and IL-8 by endothelial cells. 20 In addition, in a cell culture model of simulated warm ischemia, inter-endothelial cell gap formation was prevented by a competitive TLR4 antagonist, implicating a direct link between pulmonary edema and TLR signaling. 19 …”
Section: Epithelium and Endotheliummentioning
confidence: 97%
“…We developed a model of simulated cold lung IRI with human umbilical vein endothelial cells (HUVECs) and showed that replacing cold media with Perfadex resulted in rapid alteration in actin cytoskeleton associated with gap formation in the endothelial monolayer (22). To determine the impact of exposure to 40 ppm NO on endothelial behavior, human pulmonary microvascular endothelial cells (HMVECs) were grown to confluence in nine P35 dishes.…”
Section: Cell Culture Model Of Cold Ischemiamentioning
confidence: 99%
“…Additionally, in the lung transplant setting, donor lungs are inflated with oxygen and stored in cold preservation solution. Previously, two studies have used cell culture to simulate lung transplantation (7,8). These studies suggested that detailed molecular mechanisms could be explored using such models.…”
Section: Introductionmentioning
confidence: 99%